The Effectiveness of Talking Chips Technique to Improve Student English Speaking Skill at MTs Al-Muttaqin Rengging - Ashriyah, Sa'adatus Septi; Putri, Aprilia Riyana (Universitas Nurul Jadid, 2025)
This study aimed to examine the effectiveness of the Talking Chips technique in improving the English-speaking skills of eighth-grade students at MTs Al-Muttaqin Rengging, Jepara. A quantitative approach with a quasi-experimental design, specifically the non-equivalent control group design, was employed in this research. The participants consisted of two classes: class VIII A as the experimental group and class VIII B as the control group. The data were collected using oral speaking tests (pre-test and post-test) assessing five aspects of speaking: fluency, vocabulary, grammar, pronunciation, and comprehensibility. The findings revealed a significant improvement in the speaking performance of students taught using the Talking Chips technique compared to those taught using conventional methods. The results indicate that the Talking Chips technique effectively enhances students’ speaking abilities, particularly by promoting active participation and boosting their confidence in communicating in English. Therefore, this technique can be considered a useful cooperative learning strategy for developing communicative competence in English as a Foreign Language (EFL) classrooms.